The NHS and market forces in healthcare: the need for organisational ethics. Issue 1 (19th October 2012) - Frith, Lucy
Abstract : The NHS in England is an organisation undergoing substantial change. The passage of the Health and Social Care Act 2012, consolidates and builds on previous health policies and introduces further 'market-style' reforms of the NHS. One of the main aspects of these reforms is to encourage private and third sector providers to deliver NHS services. The rationale for this is to foster a more competitive market in healthcare to encourage greater efficiency and innovation. This changing healthcare environment in the English NHS sharpens the need for attention to be paid to the ethical operation of healthcare organisations. All healthcare organisations need to consider the ethical aspects of their operation, whether state or privately run. However, the changes in the type of organisations used to provide healthcare (such as commercial companies) can create new relationships and ethical tensions. This paper will chart the development of organisational ethics as a concern in applied ethics and how it arose in the USA largely owing to changes in the organisation of healthcare financing and provision. It will be argued that an analogous transition is happening in the NHS in England. The paper will conclude with suggestions for the development of organisational ethics programmes to address some of the possible ethical issues raised by this new healthcare environment that incorporates both private and public sector providers.